INOVASI PRODUK: PENINGKATAN LAYANAN DAN DESAIN KEMASAN KREATIF DI INDUSTRI FLORIST KOMUNITAS PENCINTA ANGGREK INDONESIA CABANG BALIKPAPAN - Hamijaya, Prasis Damai Nursyam; Satyaninggrat, Luh Made Wisnu; Alif, Muh. Ikhsan (Jurnal Abdi Insani, 2025)
This community service initiative is a collaboration with the Balikpapan Branch of the Indonesian Orchid Lovers Community (PAI). The activity aims to improve the competitiveness of local orchids in Balikpapan through product innovation. The main challenges faced by the partner, Bakoel Kembang Ruhui Rahayu, are low service and packaging diversification, a lack of product information, and suboptimal branding. These conditions hamper market penetration and limit the selling value of orchid products. Through product innovation, it is hoped that orchids will have more competitive added value. The objective of this activity is to equip partners with the skills to design creative and informative services and packaging, as well as improve the quality of product displays. The implementation method includes practice-based training, starting from researching service and packaging trends, material selection, design planning, and packaging simulations with QR code integration. Evaluation was carried out through participant feedback and testing the feasibility of packaging in the local market. The results of the activity showed an increase in participants' skills in designing market-standard service and packaging models for young, juvenile, and mature orchids. All participants were able to create packaging designs with clear labels and product information. Improvements in services related to product innovation were recorded significantly, such as Custom Bouquets and Hampers (225%), Classes and Workshops (200%) and Online Sales (160%). Participants also began integrating packaging with digital marketing strategies to increase sales reach. Positive impacts were seen in the increased variety of services and the enhanced professional image of the products. In conclusion, this product innovation training successfully achieved its target, expanded partner services, and increased the market appeal of local orchids.